2009
DOI: 10.3198/jpr2008.10.0618crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Endeavor’ Winter Barley

Abstract: ‘Endeavor’ (Reg. No. CV‐341, PI 654824), a two‐rowed winter malting barley (Hordeum vulgare L.), was developed and submitted for release in 2007 by the USDA–ARS, Aberdeen, ID, in cooperation with the University of Idaho Agricultural Experiment Station. Endeavor is a selection from the cross ORWM8406/‘Harrington’. ORWM8406 has the pedigree ‘Carstens’/‘Riso’ mutant 1508 (F1)//‘Cossack’. Riso mutant 1508 is an ethyleneimine‐induced mutant of ‘Bomi’. Progenitors of ORWM8406 are all European barleys. Harrington is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Lontra outperformed Wintmalt for plump kernels (∼6% higher at each site) and Lontra was only out of specification for 1 station-year. Lontra was advanced into the Oregon Malt Elite Trials (OMELT) for the 2020 and 2021 harvest years and benchmarked against three AMBA recommended cultivars-'Endeavor', 'Thunder', and Wintmalt (Hayes et al, 2019;Obert et al, 2009). Data from the replicated field trials in Corvallis are shown in Table 2.…”
Section: Agronomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lontra outperformed Wintmalt for plump kernels (∼6% higher at each site) and Lontra was only out of specification for 1 station-year. Lontra was advanced into the Oregon Malt Elite Trials (OMELT) for the 2020 and 2021 harvest years and benchmarked against three AMBA recommended cultivars-'Endeavor', 'Thunder', and Wintmalt (Hayes et al, 2019;Obert et al, 2009). Data from the replicated field trials in Corvallis are shown in Table 2.…”
Section: Agronomicsmentioning
confidence: 99%
“…Lontra was advanced into the Oregon Malt Elite Trials (OMELT) for the 2020 and 2021 harvest years and benchmarked against three AMBA recommended cultivars—‘Endeavor’, ‘Thunder’, and Wintmalt (Hayes et al., 2019; Obert et al., 2009). Data from the replicated field trials in Corvallis are shown in Table 2.…”
Section: Characteristicsmentioning
confidence: 99%
“…All statistical analyses were conducted using R version 3.5.1 (R Core Team). In the Oregon, WMBT, and Idaho trials, Lightning was compared with 'Endeavor' (Obert et al, 2009; PI 654824) and 'Wintmalt'. In the New York trials, Lightning was compared with 'KWS Scala' and Endeavor.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Although spring barley is dominant in current production, advantages of winter barley or facultative barley planted in fall are clear and could be more important in drought-stricken areas or areas with traditionally less precipitation during the growing season. Current commercial winter malting barley cultivars include 'Charles' and 'Endeavor' from the USDA-ARS, Aberdeen, ID (Obert et al, 2006(Obert et al, , 2009, 'Wintmalt' introduced from LimaGrain Cereal Seeds LLC, and 'Thunder' from Oregon State University. With the challenges of market demands, climate change, biotic and abiotic stresses, and production efficiency, barley breeding needs to respond to those challenges.…”
Section: Introductionmentioning
confidence: 99%